Synthesis of thorium sol for fabricating fuel kernels - Wang, Feng-Xia; Yan, Chao; Cao, Chang-Qing; Wang, Peng; Huang, He; Jiang, Hai-Tao; Lin, Jun; Cheng, Zhi-Xuan; Zhu, Zhi-Yong (Nuclear science and techniques, 2017)
To fabricate thorium-based fuel kernel for solid fuel molten salt reactor,a component of tri-structural isotropic fuel particles is mostly based on sol-gel method.The preparation of thorium sol is an important step for fabrication of thorium-based fuel kernels,such as thorium carbide and thorium oxide.The gel quality affects the gel particle dispersion and the final products.In this work,thorium sols were prepared using Th（NO3）4 and NH3·H2O by sol-gel method.The effects of thorium concentration,mole ratio of NH4^＋/NO3^- and reaction temperature on the pH,viscosity,turbidity,particle size and the thorium sol distribution were investigated.The results show that the viscosity and turbidity increased with the NH4^＋/NO3^- ratio;the turbidity and colloidal particle size increased with the reaction temperature,which affected little the sol viscosity;the sol viscosity increased with the thorium concentration,which virtually did not change the turbidity;and the particle size decreased and the size distribution narrowed with increasing thorium concentration.The sol could be stored at room temperature for one day without significant property changes.Thorium gel spheres of good quality were prepared at 60℃ with the NH4^＋/NO3^- ratio of 75-85% and the thorium concentration of 1.2-1.4 mol/L.